Seismic imaging of the Alpine Fault near Inchbonnie, New Zealand. Issue 1 (31st January 2013) - Carpentier, S. F. A.; Green, A. G.; Langridge, R.; Hurter, F.; Kaiser, A.; Horstmeyer, H.; Finnemore, M.
Abstract : [1] The transpressive Alpine Fault is the boundary between the Pacific and Australian plates across the South Island of New Zealand. Earthquakes on the Alpine Fault and related structures pose a serious risk to many urban centers, including the city of Christchurch. Although it is a major feature on satellite images, the Alpine Fault is a difficult target for surface studies along much of its length; it mostly traverses densely forested and mountainous terrain and where it occurs in the lowlands it is usually covered by recent sediments. To investigate the Alpine Fault at a rare accessible location (Inchbonnie), we have acquired high‐resolution seismic reflection data along five 380–1200 m long lines. Images produced from these data reveal a glacially overdeepened valley containing a thick sequence of diverse glacigenic sediments that have been disrupted by three en echelon strands of the principal Alpine Fault and several secondary fault strands. Based on their seismic facies, the sedimentary sequence is interpreted to comprise basal lacustrine beds overlain successively by alluvial‐colluvial deposits that possibly include the remnants of large landslides, deltaic‐fan units, and braided river gravels. Whereas the principal Alpine Fault strands disrupt the entire post‐glacial sedimentary section and likely offset basement at depths up to 400 m, most of the secondary faults either merge with the principal fault strands at shallow depths or are surficial features limited to the sedimentary section. Key Points: Seismic reflection imaging reveals a system of broad en echelon faulting Five parallel seismic lines lead up to a pseudo 3‐D model of the Alpine Fault A consistent interpretation is made of paleosedimentation in a glacial valley